Utilization of Chicken Feather Waste as a Source of Additional Protein in Ruminant Feed - Isthar Bismuth Sururi; Daud Mustofa Munief; Fathuddin Izzul Haqq Al Hamas; Muhammad Amin Rahmadani; Zaki Sidqi Aaliyya; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2022)
The food needs of the Indonesian people are increasing along with the increase the number of human population. One of the food needs of the community is meat, which is quite accommodated with chicken meat. This triggers an increase in chicken meat production by farmers every year. This increase also affects the waste produced, especially poultry feather waste (chicken). The increasing waste of chicken feathers has become the center of attention of researchers to process it into something more useful. The purpose of this study was to describe the making process of poultry feather waste (chicken) to reduce the impact of chicken feather waste pollution on the environment, by processing it into a protein source for ruminant feed in the form of Chicken Feather Hydrolyzate (CFH). The type of research is descriptive, with a qualitative approach. The focus of the description is on the processing of chicken feather waste into CFH as a source of protein for ruminant feed. The data collected by observation and literature study. The observation showed that chicken feather waste contained the protein needed in ruminant feed. Meanwhile, the results of the litterature study show that the ruminant needs at least 12% protein from their feeds. From this research, it can be concluded that chicken feather waste can be processed into a protein source for ruminants in the form of CFH.